A Highly Durable Rubber‐Derived Lithium‐Conducting Elastomer for Lithium Metal Batteries. Issue 16 (31st March 2022) - Shi, Yongzheng; Yang, Na; Niu, Jin; Yang, Shubin; Wang, Feng
Abstract: Elastomers offer attractive advantages over classical solid‐state electrolytes in terms of ensuring stable interfacial contact and maintaining fatigue durability, but the low ionic conductivity obstructs their practical applications in long‐life lithium metal batteries. In this work, rubber‐derived lithium‐conducting elastomer has been developed via sulfur vulcanization of nitrile butadiene rubber with a polymerizable ionic liquid to provide both high resilience and dramatically improved ionic conductivity. Owing to the chemically crosslinked network between rubber chains and ionic liquid fragments generated during vulcanization, the elastic lithium‐conductor achieves high resilience of 0.92 MJ m −3, superior cyclic durability of 1000 cycles at 50% strain, and high room‐temperature ionic conductivity of 2.7 × 10 −4  S cm −1 . Consequently, the corresponding solid‐state lithium/LiFePO4 battery exhibits a high capacity of ≈146 mAh g −1 with a high capacity retention of 94.3% for up to 300 cycles. Abstract : By virtue of a chemically crosslinked network via vulcanization approach, the rubber‐derived lithium‐conductor achieves high resilience of 0.92 MJ m −3, superior fatigue durability of 1000 cycles at 50% strain, and high room‐temperature ionic conductivity of 2.7 × 10 −4  S cm −1 . This unique lithium‐conducting elastomer enables intimate contact and fast lithium‐ion transport, resulting in long‐life and high‐performance solid‐state lithium metal batteries.